2004
DOI: 10.1200/jco.2004.08.085
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Outcome Characteristics of Children With Adrenocortical Tumors: A Report From the International Pediatric Adrenocortical Tumor Registry

Abstract: Childhood ACTs occur predominantly in females and almost always causes clinical signs. Complete resection is required for cure. Residual or metastatic disease carries a poor prognosis. Our results demonstrate the feasibility of a disease-specific database for obtaining meaningful clinical and outcome information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
526
4
55

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 450 publications
(604 citation statements)
references
References 32 publications
19
526
4
55
Order By: Relevance
“…Although the penetrance of ACC in R337H carriers is relatively low (only 10%), it represents a 20,000-fold increased risk for ACC based on worldwide estimates (Michalkiewicz et al, 2004;Figueiredo et al, 2006). The incomplete penetrance may be related in part to the inability of R337H to act as a dominant negative regulator of wild-type p53.…”
Section: Li-fraumeni Syndrome and Inherited P53 Mutationsmentioning
confidence: 99%
“…Although the penetrance of ACC in R337H carriers is relatively low (only 10%), it represents a 20,000-fold increased risk for ACC based on worldwide estimates (Michalkiewicz et al, 2004;Figueiredo et al, 2006). The incomplete penetrance may be related in part to the inability of R337H to act as a dominant negative regulator of wild-type p53.…”
Section: Li-fraumeni Syndrome and Inherited P53 Mutationsmentioning
confidence: 99%
“…25 A tumor registry for ACC has now been established to facilitate continued clinical and biologic studies and to prepare an infrastructure for subsequent clinical trials of prevention and early detection. 26 …”
Section: Adrenocortical Carcinoma and Retinoblastoma As Models Of Thementioning
confidence: 99%
“…Michalkiewicz et al reported that patients reported from other countries rarely had been tested for constitutional or somatic TP53 mutation except Brazilian patients [13]. We recommend the patients with adrenocortical carcinoma, especially the girls to be tested for the status of TP53 gene.…”
Section: Discussionmentioning
confidence: 99%
“…Virilizing adrenal tumors show growth acceleration, deepening of voice, premature pubic and axillary hair development, and clitoral or penile enlargement. Isolated Cushing syndrome, Conn syndrome, and pure feminization occur very rarely in children [6,13,18,24].…”
Section: Introductionmentioning
confidence: 99%